Application of Carbon Nanomaterials in Gene Delivery for Endogenous RNA Interference In Vitro and In Vivo - Li, Lanying; Wen, Yanli; Xu, Qin; Xu, Li; Liu, Dong; Liu, Gang; Huang, Qing (Current Pharmaceutical Design, 2015)
Knocking down expression by small interfering RNA (siRNA) has shown high affinity, specificity and potency in silencing target gene sites. For effective endogenous RNA interference (RNAi), proper siRNA delivery vehicles are essential, to take the siRNA inside cells and protect them during the circulation. Carbon nanomaterials (CNMs) have been successfully applied in biomedicine and biosensor based on their ultra-high surface functionalization and nucleic acid molecular loading capacity. Recently, CNMs have drawn considerable research interest and expectation as potential non-viral vectors for siRNA delivery. Here we reviewed the recent application of CNMs in gene delivery for RNAi, mainly about fullerenes, carbon nanotubes (CNTs) and graphene.
Keywords: graphene